A sequential approach for the economic evaluation of new CO2 capture technologies for power plants. (May 2019) - Guandalini, Giulio; Romano, Matteo C.; Ho, Minh; Wiley, Dianne; Rubin, Edward S.; Abanades, J. Carlos
Highlights: Method for calculating breakeven CAPEX and OPEX and minimum CCA of novel technologies. Simplified mass and energy balance and economic model for greenfield coal power plant. Method applied on selected technologies for CO2 capture in coal power plants. Limiting the efficiency penalty of novel capture systems main driver for technology developers. CCA mainly affected by increased CAPEX of conventional units caused by efficiency penalty. Abstract: This paper describes a simplified method to estimate the cost of CO2 avoided for a power plant with a novel CO2 capture system based on only a limited number of fundamental input parameters used to establish basic mass and energy flows for the plant. The cost calculation method follows a sequential approach, estimating first the cost and efficiency penalty impacts of those elements of the plant that are standard and well characterized. We then define the cost gap allowed for the novel elements to break even against a benchmark plant. This method allows one to estimate: (i) the maximum cost reduction potential that a novel CO2 capture technology can achieve with respect to a benchmark technology, and (ii) target breakeven costs for technology developers in the form of combinations of CAPEX and OPEX for a novel capture technology needed to make the technology competitive with the benchmark system. Case studies are presented applying the proposed method to post-combustion and oxy-combustion capture systems, showing that: (i) a clear relationship exists between the breakeven costs and the efficiency penalty caused by the CO2 capture process, mainly because of its effect on the specific capital cost ($/kWe ) of the conventional power plant components; and (ii) the minimum cost of CO2 avoided is closely related to the capture system efficiency penalty. For the case study assumptions, avoidance costs vary from ∼20 $/tCO2 to ∼60 $/tCO2 for efficiency penalties ranging from 2.7% pts to 11% pts, respectively.